Derivation of the Buffalo Concussion Physical Examination risk of delayed recovery (RDR) score to identify children at risk for persistent postconcussive symptoms. Issue 24 (11th September 2021) - Haider, Mohammad Nadir; Cunningham, Adam; Darling, Scott; Suffoletto, Heidi N; Freitas, Michael S; Jain, Rajiv K; Willer, Barry; Leddy, John J
Abstract : Objective: The Buffalo Concussion Physical Examination (BCPE) is a brief, but pertinent physical examination designed for the subacute, outpatient assessment of concussion. The purpose of this study was to perform the BCPE on a larger sample and derive a scoring system to identify children at risk for Persistent Post-Concussive Symptoms (PPCS, recovery ≥30 days). Methods: This prospective, observational cohort study from September 2016 to March 2019 was performed at three university-affiliated concussion clinics. Male and female children (n=270, 14.92±1.86 years, range 8–18, 38% female) were diagnosed with a concussion within 14 days of injury and followed-up until recovery. Logistic regression was used with history and physical examination variables to predict PPCS and a weighted scoring metric was derived. Results: Out of 15 predictor variables, the main effects of 1 preinjury variable (≥3 previous concussions), 2 injury characteristic variables (days-since-injury and type-of-injury), 3 physical examination variables (orthostatic intolerance (OI), vestibulo-ocular reflex (VOR) and tandem gait) and 2 interaction terms (OI/VOR and tandem gait/type-of-injury) produced a score that was 85% accurate for identifying children with low-risk, medium-risk and high-risk for PPCS on cross-validation. Conclusion: The Risk for Delayed Recovery (RDR)-Score allows physicians in an outpatient setting to more accurately predict which children are at greater risk for PPCS early after their injury, and who would benefit most from targeted therapies. The RDR-Score is intended to be used as part of a comprehensive assessment that should include validated symptom checklists, mental health history and adjunct testing (eg, cognitive or physical exertion) where clinically indicated.